Improving the results of science learning through learning method discovery guided in students class iv sdn 29 koto panjang district ranah pesisir - Muchlidah Muchlidah (Jurnal Ilmiah Pendidikan Scholastic, 2017)
This study aims to improve science learning outcomes of fourth grade students of SDN 29 Koto Panjang, Ranah Pesisir sub district using guided discovery learning method. This type of research is a classroom action research. The subjects of this study were students of grade IV-A SDN 29 Koto Panjang, Ranah Pesisir sub-district, which consisted of 28 students, consisting of 13 male students and 15 female students. Researchers used an action research model from Kemmis and Taggart. This study was conducted in two cycles of action. In the first cycle is done in one meeting while in the second cycle two meetings. At each cycle there are activities of planning, implementation, observation, and reflection. The instruments used are observation and test sheets. Prior to use in the study, tests were empirically validated and expert judgment. Test reliability is calculated using AlphaCronbach. The observational data were analyzed descriptively qualitatively while the test result was analyzed descriptively quantitative percentage. The results of the first cycle study showed that the percentage of students whose value above the new KKM reached 71.43%, so it still can not achieve the criteria of research success. In cycle II, the steps of applying discovery learning method to improve student's success are done by giving motivation, dividing the smaller group members and heterogeneous member, and giving the opportunity to do group presentation on the result of the practice in front of the class. The percentage of student scores above KKM in cycle II increased to 89.29%. Based on the results of the research, it can be seen that guided discovey method can improve science learning outcomes.